Hubungan karakteristik mahasiswa dengan minat bekerja di pertanian: studi kasus Fakultas Pertanian, Universitas Sintuwu Maroso - Ahmad, Nurmayanti H; Managanta, Andri Amaliel; Toyip; Mowidu, Ita (Analisis Kebijakan Pertanian, 2024)
Agricultural development in Indonesia faces various problems, including the young generation’s low interest in agriculture, caused by push and pull factors. This research aims to analyze the relationship between student characteristics, family factors, community factors, and students’ interest in working in the agricultural sector. The study was conducted from July to October 2022, and 94 students from the Department of Agrotechnology, Faculty of Agriculture, Sintuwu Maroso University were selected using a simple random sampling technique. Analysis was carried out descriptively and using the Spearman rank correlation test. The research results show that student characteristics (gender, cultivation experience, regional origin) and family characteristics (parents’ occupation, land ownership) have a significant relationship with students’ interest in working in agriculture. Community factors (relationships between neighbors and local culture) also have a significant relationship with students’ desire to work in agriculture. The policy implications of this research results emphasize the need for a comprehensive response from the government, both at the central and regional levels, to increase student interest and involvement in the agricultural sector, which is the main pillar of the economy and social life.